2007
DOI: 10.1111/j.1399-5448.2007.00255.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prevalence of type 1 diabetes in children aged <15 yr in Castilla-Leon (Spain)

Abstract: Castilla-Leon appears to have one of the highest incidences of childhood type 1 diabetes in Spain, with recent incidence approaching those of some northern European countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
11

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 27 publications
1
8
0
11
Order By: Relevance
“…Our data show that the average prevalence of T1DM in the pediatric population (aged 0-18) in the analyzed period (2008-2013) was 1.26 cases per 1000 subjects. This result is lower than the SEARCH study (1.82/1000) but comparable with previously published data in Spain [13][14][15]. Incidence peaked at 22/100,000 around puberty, as reported worldwide [14].…”
Section: Discussionsupporting
confidence: 89%
“…Our data show that the average prevalence of T1DM in the pediatric population (aged 0-18) in the analyzed period (2008-2013) was 1.26 cases per 1000 subjects. This result is lower than the SEARCH study (1.82/1000) but comparable with previously published data in Spain [13][14][15]. Incidence peaked at 22/100,000 around puberty, as reported worldwide [14].…”
Section: Discussionsupporting
confidence: 89%
“…Para España, el Atlas de la IDF da una incidencia global de 20,6 en menores de 15 años. En años anteriores se han publicado datos de casi todas las comunidades autónomas [2][3][4][5][6][7][8][9][10][11][12][13] . La incidencia en la comunidad más afectada -CastillaLa Mancha (27,6) 3 -duplica a la de menor incidencia -Asturias (11,5) .…”
Section: Resultsunclassified
“…En Europa se ha descrito un gradiente norte-sur en la incidencia de DM1 23 , con mayor incidencia en los países del norte, con la excepción de Cerdeña 24 . Sin embargo, los datos de las comunidades españo-las van en sentido contrario [2][3][4][5][6][7][8][9][10][11][12][13] . En Navarra, no disponemos de datos previos al respecto.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…T1D is a global health problem, affecting mainly children [1]. The Diabetes control and complication trial demonstrated that intensive insulin therapy achieved better blood glucose control than conventional therapy and reduced the severity and frequency of micro-and macro vascular complications [2,3].…”
Section: Introductionmentioning
confidence: 99%